The Competency in Marketing Competitive Advantage Development Model of Cultural Tourism Four Dvaravati Provinces - Sungrugsa, Narin; Rattanapongpinyo, Thaninrat; Pwongsa, Phakamas (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
This is a research of reseaech and development methodology, aiming to 1) study the situations of market competition, 2) analyze the model of competency in marketing competitive advantage, 3) evaluate and improve the model of competency in marketing competitive advantage. The research processes were divded into 4 stages: 1 study related basic dats, 2) desigh and generate the draft model, 3) try out the draft model, 4) evluate, improve and finally propose the model. The research instruments were an interview questionnaire, a guideline for in-depth interviewing, a guideline for focus group discussion, docomentary analysis and non-participant observation. the collected data was statistically analyzed with a statistical computer program package and presented in percentage, mean, and standard deviation. The qualitative data was then analyzed by the technique of content analysis. Research findings were as follow: 1) Most of the four Dvaravati Provinces were ready to support the development of culturl tourism. However, their processes of markitng and public relations were considered passive performances. Therefore, these should be carried out in more seriously and continuously proactive ways. Thai and foreign tourists had their opportunities and trends to increasingly visit the four provinces. Their motivation for this tourism was evaluated at a high level. 2) The one model of development was constructed and named "DVARVATI Model" , and these alphabet definitions came from (1) D=Different Marketing, (2) V=Visual for Variation, (3) A=Attraction of Tourism, (4) R=Responsibillity for Community, (5) A=Amenity in Tourism, (6) V=Variety of Market Tourism, (7) A=Activity of Marketing (8) , T=Techonology for Tourism, (9) I=Information System for Maketing. 3) The pre-test score of the knowledge and understanding of stakeholders before training was at the moderate level. After the training the post-test score was at the high level. The post-test is significantly higher than that of the pre-test score at p-value = .05 The development of marketing plan included maketing strategies and tourism strategic issues of cultral tourism for the four Dvaravati Provinces.